Determine the Optimal Recovery Policy for Returned Products: An Analytical Approach - Liu, Chen (2007)
Recovery of returned products is an emerging business area, which has received special attention from environmental as well as economic point of view. Effective product recovery can help to reduce the demand for raw materials, energy consumption, and landfill space. Perhaps most importantly, from a business perspective, it can contribute to the overall profitability of the company significantly. The profitability of product recovery operations depends on the quality and volume of product returns as well as the demand for recovered products however these factors are not directly controllable. Aims to investigate to what extent the benefit of product recovery can be captured seven scenarios are developed and discussed with an analytical approach. The costs of possible recovery options are analyzed for determining the optimal recovery policy in different scenarios. With the aid of Linear Programming model more uncertainties associated with product recovery are considered to give more quantitative insights regarding complex situation. By conducting a number of experiments the factors that impact the choice of optimal recovery policy are identified, which including the timing, volume and quality of returned product, the price fluctuation of recovered products in the market, and the resell potential of secondary market. The optimal recovery policies and the performance of which are also discussed.